Identifying the participants: reference in television news. (May 2016) - Feng, Debing
This article presents a generalized model of reference relations in the discourse of television news based on Montgomery's principles of intelligibility, Halliday and Hasan's reference cohesion, Martin's identification system, Tseng's cohesive reference and some intersemiotic models. Reference in television news involves reference patterns from the verbal track (verbal reference), the visual track (visual reference) and across the two tracks (visual–verbal reference). Based on the categorization of verbal reference, this study classifies visual reference as personals (such as visual reappearance), demonstratives (such as proximity and direction) and comparatives (such as similarity and difference). Reference across visual and verbal tracks includes three general types of visual–verbal reference, i.e. complementary, visual-as-bridge and parallel, among others. Through these patterns of reference and their reference chains, participants in television news can be tracked and identified. This model is applied to a comparative analysis of two news items broadcast separately by BBC's News at Ten and CCTV's News Simulcast . Differences and their implications are presented and discussed.